Challenges Faced by Administrative Personnel in Drafting Formal English Letters - Dewi Yanti; Edison Hamid (EXPOSE (Journal of English Education and for Specific Purpose), 2023)
This study investigates the linguistic, technical, and organizational challenges encountered by administrative personnel in drafting formal English letters within higher education settings. Using a qualitative descriptive design, data were collected through semi-structured interviews and document analysis involving twelve administrative staff from three institutions. The findings reveal three major categories of challenges. Linguistically, participants demonstrated limited mastery of formal vocabulary, frequent grammatical errors, and a strong tendency toward literal translation. Technically, the letters showed inconsistent formatting, non-standardized templates, and irregular application of international writing conventions. Organizationally, the lack of training opportunities, demanding workloads, and absence of proofreading mechanisms significantly contributed to recurring errors. These findings highlight that administrative writing difficulties are not solely linguistic but are shaped by systemic institutional conditions. The study contributes to English for Specific Purposes (ESP) research by offering an integrated view of administrative writing demands and underscores the need for targeted training, standardized templates, and structured support systems. Recommendations for institutional improvement and directions for future research are also presented.